Adolescent mothers affected by HIV and their children: a scoping review of evidence and experiences from sub-Saharan Africa - Toska, Elona (Glob Public Health, 2020)
While adolescents have received increasing attention in the global HIV response and international strategies and commitments, adolescent mothers and their children remain largely overlooked in research, funding and, programming for health-related outcomes. We conducted an extensive scoping review of current evidence on the experiences of adolescent mothers affected by HIV and their children in this region. We included published literature and conference abstracts, complemented by consultations with key stakeholders, and a review of documents through grey literature searching. First, we summarise the experiences of adolescent mothers and their children related to HIV and key health and development indicators. The syndemic of early motherhood and HIV in sub-Saharan Africa increases the vulnerability of adolescent mothers and their children. We then highlight lessons from a series of promising programmes focused on supporting adolescent mothers through novel approaches. In sub-Saharan Africa, supporting adolescent mothers living in high HIV-risk communities is critical not only to eliminate HIV/AIDS, but also to attain the Sustainable Development Goals. While research on and programming for adolescent mothers and their children is growing, the complex needs for this vulnerable group remain unmet. We conclude with evidence gaps and programming priorities for adolescent mothers affected by HIV and their children.